2020
DOI: 10.1177/0892705720939141
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and processing properties of recycled PET and LDPE-HDPE composite materials for building components

Abstract: Although several reports can be found in the literature about the recycling of plastic materials, only a few focus on recovering and molding them in a new process. Plastic material blends can be fabricated using several techniques, which allows the molding of a compound adaptable to each needed performance. This fact favors the recycling by allowing the use of mixed wastes without major processes, avoiding expensive treatments. This research work analyzes the mechanical properties of a material conformed by 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although several reports can be found in the literature about the recycling of plastic materials, only a few focus on recovering and molding them in a new process. Laria et al (2020) analyzed the mechanical properties of a material formed by 100% recycled plastics: polyethylene terephthalate and low-/high-density polyethylene without previous separation or washing and drying pretreatments. Its macro and microscopic structure were studied and described, and formulations of different compound rates were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports can be found in the literature about the recycling of plastic materials, only a few focus on recovering and molding them in a new process. Laria et al (2020) analyzed the mechanical properties of a material formed by 100% recycled plastics: polyethylene terephthalate and low-/high-density polyethylene without previous separation or washing and drying pretreatments. Its macro and microscopic structure were studied and described, and formulations of different compound rates were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The waste in the form of plastic has been increasing day by day and prediction has been made that it will be in abundance in near future [1]. The disposal of solid plastic waste through burning will cause more pollution due to release of toxic gases [2].…”
Section: Introductionmentioning
confidence: 99%
“…The waste in the form of plastic has been increasing day by day and prediction has been made that it will be in abundance in near future. 1 The disposal of solid plastic waste through burning will cause more pollution due to the release of toxic gases. 2 Commercially the thermoplastics are being recycled but recycling of thermosetting has many challenges (such as technological and cost-effective issues).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the reuse of waste plastics for several applications has been reported [4,5]. For example, Laria et al [4] studied the mechanical properties of waste plastics composed of a mixture of waste thermoplastics for use as building components. Further, Bertelsen et al [5] reported the cracking behavior of Polymers 2021, 13, 1058 2 of 11 concrete substrates containing commercially available polypropylene fibers and recycled polyethylene (PE) fibers obtained from discarded fishing nets.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is crucial to develop MR processes for used plastic products to prevent environmental pollution and the depletion of virgin resources [ 3 ]. Recently, the reuse of waste plastics for several applications has been reported [ 4 , 5 ]. For example, Laria et al [ 4 ] studied the mechanical properties of waste plastics composed of a mixture of waste thermoplastics for use as building components.…”
Section: Introductionmentioning
confidence: 99%